Innovative Fly-Ash-Based Soil Crust Rehabilitation: Enhancing Wind Erosion Resistance in Gravel-Layered Desert Mining Areas - Yu Zheng; Weiming Guan; Jingwen Li; Zhenqi Hu; Gensheng Li; Meng Xie; Xuewei Zhang (Land)
Gravel layers are vital ecological barriers in Gobi Desert mining areas. However, open-pit activities increase wind and soil erosion. Thus, the effects of fly ash addition, water content, and compaction on the shear strength and wind erosion resistance of soil crusts were explored by compaction tests, direct shear tests, and wind tunnel experiments. (1) The results of the direct shear test and vane shear test show that the modified soil sample achieved the maximum shear strength under the conditions of 15% fly ash content, 13% water content, and 3 compaction cycles. (2) The results of the wind tunnel test indicate that the wind erosion resistance of the gravel layer soil crust was improved after fly ash treatment. Compared to the untreated soil crust, the wind erosion amount of the treated soil was reduced by 23%. (3) Microscopic analysis revealed that hydration products from fly ash filled the soil pores, enhancing particle bonding and soil structure, using a scanning electron microscope (SEM) and an X-ray fluorescence spectrometer (XRF). (4) Considering the water scarcity in the Eastern Junggar Coalfield of China, a revised rehabilitation scheme was selected, involving 11% water content and single compaction, offering a balance between performance and economic efficiency. This study provides a novel approach to gravel layer restoration in arid mining regions using fly ash as a soil stabilizer, offering a sustainable method to enhance wind erosion resistance and promote fly ash recycling.